Global forces and local currents in Argentina's science policy crossroads: restricted access or open knowledge - Etchichury, Horacio Javier; Pacheco, Marcela Carmen (2024)
Fil: Etchichury, Horacio Javier. Universidad Nacional de Córdoba. Facultad de Derecho; Argentina.